Project lift: investment committee paper on the gym group - company analysis - Bosio, Federico (2024)
The following report summarises the main outcome of the preliminary analysis conducted on The Gym Group (TGG), a leading UK provider of low-cost fitness services, for the evaluation of a Leveraged Buy Out (LBO) acquisition by a Private Equity Fund in the form of an Investment Committee Paper (ICP). The first part (“Group Part”) consists of a complete overview of the core components of the analysis and represent a summary of the complete ICP itself. Subsequently, an in-depth analysis (“Individual Part”) of the Company itself is presented, providing more detailed insights.